Efektivitas Pilkada Serentak Tahun 2020 di Tengah Pandemi Covid-19 Indonesia - Ika Prawitasari; Dewi Erowati (Mahesa Research Center, 2021)
This study examines effectiveness 2020 simultaneous regional elections in the midst of Covid-19 pandemic. In addition, indicators of success Pilkada are integrity organizers and public participation in exercising their voting rights. Therefore, looking at 2020 Pilkada which was held in midst Covid-19 pandemic is still an important discourse. This study used descriptive qualitative method. Data collection techniques use primary data obtained from webinars on local political democracy during pandemic and secondary data by citing books, journals, documents and printed media, as well as other supporting materials. The results showed that the 9 December 2020 Pilkada had several threats and opportunities, including; First, threat of high number of positive cases of Covid-19, limited time, process updating voter data, technical guidance for ad hoc administrators, logistical budgets, education and political outreach. Second, opportunities for technology and information as means of political education and political socialization. Third, organizing regional elections by using e-voting, being the right recommendation, seeing use of e-voting can preserve people's voting rights and inhibit spread of Covid-19.